2021
DOI: 10.1186/s13002-020-00423-y
|View full text |Cite
|
Sign up to set email alerts
|

Wild food plants and fungi sold in the markets of Luang Prabang, Lao PDR

Abstract: Background Open air markets hold an important position for ethnobiologists. In Southeast Asia, they are seriously understudied, in spite of their incredible biocultural diversity. In order to fill this gap we recorded plants and fungi sold in the open air markets of Luang Prabang, Lao PDR. Methods The markets were visited 38 times in four seasons: the dry season, early monsoon, mid-monsoon, and end-of-monsoon, at least 8 times per season. All items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 61 publications
3
28
1
Order By: Relevance
“…Stems and trunks are used as firewood and fencing poles. To treat snakebite and stomachache [ 48 ] Anacardiaceae Mangifera sylvatica Roxb. b Amsey KN014 4 5 Jul–Aug Mo Fruits are consumed raw and as pickles [ 49 ] Anacardiaceae Choerospondias axillaris (Roxb.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stems and trunks are used as firewood and fencing poles. To treat snakebite and stomachache [ 48 ] Anacardiaceae Mangifera sylvatica Roxb. b Amsey KN014 4 5 Jul–Aug Mo Fruits are consumed raw and as pickles [ 49 ] Anacardiaceae Choerospondias axillaris (Roxb.)…”
Section: Resultsmentioning
confidence: 99%
“…B.L.Burtt & A.W.Hill b Phrumchung sey KN012 14 0 Jul–Aug Ra Fruits consumed raw and as pickle [ 49 ] Araceae Colocasia esculenta (L.) Schott b Bozong KN016 1 1 Jan–Feb Ra Corms are boiled and consumed as snacks, curry, and soup. Leaves used to wrap dairy products and as a plate [ 21 , 23 , 48 , 49 ] Bignoniaceae Oroxylum indicum (L.) Kurz b Namkaling KN020 2 0 Aug–Sep Ra Flowers are consumed as a vegetable and used for religious purposes. To treat burns and wounds, relieve cough and gastritis [ 48 , 49 ] Combretaceae Terminalia bellirica (Gaertn.)…”
Section: Resultsmentioning
confidence: 99%
“…However, the number of WEM is less as compared to 41 WEM reported from Bhaderwah [ 11 ], and 33 [ 35 ] and 35 species [ 34 ] from Kashmir regions of Union Territory of Jammu and Kashmir. Some other studies worldwide have also recorded higher usage of WEM; 54 species from Lao PDR [ 53 ]; 40 [ 54 ] and 90 species [ 55 ] from Mexico; 56 species from Poznan [ 56 ], 32 species from Rzeszow [ 57 ], and 65 species from Mazovia [ 58 ] regions of Poland; 38 species from Budapest, Hungary [ 59 , 60 ]; 17 species from Qinling Mountains, China [ 61 ]; 22 species from Tibet, China [ 62 ]; and 29 species from Sagarmatha National Park, Nepal [ 63 ].…”
Section: Discussionmentioning
confidence: 95%
“…Various studies from different parts of the world have reported the availability of WFPs and their consumption [4]. A huge diversity of WFPs exist in Africa, Asia, and South America, and many indigenous communities still collect and consume them for nutritional as well as medicinal purposes [1,[4][5][6][7][8][9][10][11][12]. Various studies have documented the diversity of WFPs in India.…”
Section: Introductionmentioning
confidence: 99%